2016
DOI: 10.1186/s40064-016-3663-6
|View full text |Cite
|
Sign up to set email alerts
|

IL28B genotype is associated with cirrhosis or transition to cirrhosis in treatment-naive patients with chronic HCV genotype 1 infection: the international observational Gen-C study

Abstract: Background and purposeContradictory data exist on the association between host interleukin-28B (IL28B) rs12979860 genotype and liver fibrosis in patients with chronic hepatitis C (CHC). This large, international, observational study (NCT01675427/MV25600) investigated relationships between IL28B rs12979860 genotype and liver fibrosis stage in CHC patients.MethodsA total of 3003 adult, treatment-naive CHC patients were enrolled into the study. Patients made one study visit to provide a blood sample for genotypin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
1
8
0
1
Order By: Relevance
“…In countries where healthcare budgets do not currently support these treatments it remains an open question as to whether clinicians will continue to use interferon-based treatments where IL28B testing could play an important role. Additionally, IL28B polymorphisms have been reported to be predictive for transition to cirrhosis [ 21 ], fibrosis [ 22 ], hepatocellular carcinoma [ 23 ],[ 24 ], and potentially to influence clinical responses in HBV infection [ 25 ], HAV infection [ 26 ] and glucose metabolism in type 2 diabetes [ 27 ]. Furthermore due to the distinct global distribution of IL28B alleles, and the fact that IL28B has the highest reported diversity of all interferon subtypes having undergone positive selection in European and African populations [ 28 ], it seems likely that IL28B polymorphisms are important determinants in other pathological situations.…”
Section: Discussionmentioning
confidence: 99%
“…In countries where healthcare budgets do not currently support these treatments it remains an open question as to whether clinicians will continue to use interferon-based treatments where IL28B testing could play an important role. Additionally, IL28B polymorphisms have been reported to be predictive for transition to cirrhosis [ 21 ], fibrosis [ 22 ], hepatocellular carcinoma [ 23 ],[ 24 ], and potentially to influence clinical responses in HBV infection [ 25 ], HAV infection [ 26 ] and glucose metabolism in type 2 diabetes [ 27 ]. Furthermore due to the distinct global distribution of IL28B alleles, and the fact that IL28B has the highest reported diversity of all interferon subtypes having undergone positive selection in European and African populations [ 28 ], it seems likely that IL28B polymorphisms are important determinants in other pathological situations.…”
Section: Discussionmentioning
confidence: 99%
“…IL28BCC and PNPLA3GG genetic polymorphisms are considered predictors either of treatment response or progression of steatosis. In more detail, rs12979860 IL28BCC polymorphism has been associated with both, higher responses to IFN-based therapies and advanced disease in chronic HCV infection [ 8 , 9 ]. PNPLA3 encoding hydrolase against triglycerides and retinyl esters in hepatic stellate cells is associated with genetic variability.…”
Section: Introductionmentioning
confidence: 99%
“…A large international study involving 2916 patients, mostly the European Caucasian population, revealed that the increased number of the T allele was significantly associated with the prevalence of cirrhosis/transition to cirrhosis in patients infected with HCV genotype 1. This association was evident in Caucasian European patients but not in Asian, Latin American, or Middle Eastern patients infected with HCV genotype 1[ 26 ].…”
Section: Discussionmentioning
confidence: 99%